PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH DI BMT UGT NUSANTARA CABANG JOMBANG (Lembaga Pengembangan Kinerja Dosen, 2023)
This research was conducted to see how influential promotions carried out by institutions/companies were in introducing their product and how much influence service quality had in shaping customer loyalty to products and institutions/companies. This research is a quantitative research through a positivist philosophy approach. As a test material, 30 people with member status at the Jombang Branch of the BMT UGT Nusantara were used using a non-probability sampling technique. The expected data in this study were collected through questions in the form of a questionnaire. The results of the data obtained from the 30 respondents were tested using SPSS version 25 which included multiple linear regression tests, then the hypothesis was tested using the t test, then the f test and the R2 test. The results concluded that promotion and service quality implemented by BMT UGT Nusantara Jombang Branch had an influence of 36.5% on the formation of customer loyalty, based on the results of the R2 test. Based on the results of the t-count test, promotions partially have an effect of 2.395 > 2.0484 as a t-table value. Likewise, service quality also has a partial effect with a tcount of 2.228 > 2.0484 ttable. Then simultaneously, both of them have an influence on customer loyalty with an fcount value of 9.326 > 3.34 from the ftable value with a significance of 0.001 <0.05.